Basis of preventive and non-pharmacological interventions in asthma - Clemente-Suárez, Vicente Javier; Mielgo-Ayuso, Juan; Ramos-Campo, Domingo Jesús; Beltran-Velasco, Ana Isabel; Martínez-Guardado, Ismael; Navarro Jimenez, Eduardo; Redondo-Flórez, Laura; Yáñez-Sepúlveda, Rodrigo; Tornero-Aguilera, Jose Francisco (Frontiers in Public Health, 2023)
Asthma is one of the most common atopic disorders in all stages of life. Its etiology is likely due to a complex interaction between genetic, environmental, and lifestyle factors. Due to this, different non-pharmacological interventions can be implemented to reduce or alleviate the symptoms caused by this disease. Thus, the present narrative review aimed to analyze the preventive and non-pharmacological interventions such as physical exercise, physiotherapy, nutritional, ergonutritional, and psychological strategies in asthma treatment. To reach these aims, an extensive narrative review was conducted. The databases used were MedLine (PubMed), Cochrane (Wiley), Embase, PsychINFO, and CinAhl. Asthma is an immune-mediated inflammatory condition characterized by increased responsiveness to bronchoconstrictor stimuli. Different factors have been shown to play an important role in the pathogenesis of asthma, however, the treatments used to reduce its incidence are more controversial. Physical activity is focused on the benefits that aerobic training can provide, while physiotherapy interventions recommend breathing exercises to improve the quality of life of patients. Nutritional interventions are targeted on implement diets that prioritize the consumption of fruits and vegetables and supplementation with antioxidants. Psychological interventions have been proposed as an essential non-pharmacological tool to reduce the emotional problems associated with asthma.